Autoimmune disease: genetic susceptibility, environmental triggers, and immune dysregulation. Where can we develop therapies? - Kumar, Manoj; Yip, Linda; Wang, Fangyuan; Marty, Saci-Elodie; Fathman, C. Garrison (Frontiers in Immunology, 2025)
Autoimmune diseases are a diverse group of chronic disorders characterized by inappropriate immune responses against self-antigens, resulting in persistent inflammation and tissue destruction. Affecting an estimated 7–10% of the global population, these conditions include both systemic and organ-specific entities such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), type 1 diabetes (T1D), and multiple sclerosis (MS). Despite their clinical heterogeneity, autoimmune diseases share a common etiologic framework involving the convergence of genetic predisposition, environmental exposures, and immune dysregulation. Genome-wide association studies (GWAS) have identified hundreds of risk loci, most notably within the major histocompatibility complex (MHC), and highlighted the role of non-HLA genes regulating cytokine signaling, antigen presentation, and T cell tolerance. The majority of disease-associated variants lie in non-coding regulatory elements, suggesting that transcriptional dysregulation plays a central role in disease susceptibility. Yet, genetics alone does not determine disease onset—environmental factors such as infections, diet, microbiome alterations, and hormonal influences critically shape immune responses and may trigger disease in genetically susceptible individuals. Additionally, epigenetic modifications further compound these effects, creating lasting changes in gene expression and immune cell function. At the core of autoimmune pathogenesis lies immune dysregulation, particularly failure of peripheral tolerance maintained by regulatory T cells (Tregs). While Treg frequencies may appear normal in patients, emerging data indicate intrinsic signaling defects—especially impaired IL-2 receptor (IL-2R) signal durability—compromise Treg suppressive function. This dysfunction is linked to aberrant degradation of key IL-2R second messengers, including phosphorylated JAK1 and DEPTOR, due to diminished expression of GRAIL, an E3 ligase that inhibits cullin RING ligase activation. This review integrates recent insights across genetic factors, environmental triggers, and immune dysregulation to build a comprehensive understanding of autoimmune disease pathogenesis. We propose a novel therapeutic strategy targeting IL-2R signaling using Neddylation Activating Enzyme inhibitors (NAEis) conjugated to IL-2 or anti-CD25 antibodies. This approach selectively restores Treg function and immune tolerance without inducing systemic immunosuppression. By focusing on immune restoration rather than suppression, This therapy could provide an off the shelf therapy for many different autoimmune diseases.